Pengaruh Kesesuaian Kompensasi Dan Sistem Informasi Akuntansi Terhadap Kecurangan Akuntansi Dengan Pengendalian Internal Sebagai Variabel Moderasi - pasaribu, Asmia (Jurnal Riset AKuntansi dan Bisnis, 2025)
Based on the results of the study, it was concluded that Compensation suitability has a positive and significant effect on Accounting Fraud in Hospitals throughout Medan City, meaning that when the company increases the implementation of good compensation suitability, it will increase the prevention of accounting fraud, Accounting information systems have a positive and significant effect on Accounting Fraud in Hospitals throughout Medan City, meaning that when the company increases the implementation of good accounting information systems, it will increase the prevention of accounting fraud, Internal control has a positive and significant effect in moderating the effect of compensation suitability on accounting fraud in Hospitals throughout Medan City, meaning that when the company increases the provision of compensation plus the implementation of good internal control, it will increase the prevention of accounting fraud and Internal control has a positive and significant effect in moderating the effect of accounting information systems on Accounting Fraud in Hospitals throughout Medan City, meaning that when the company increases the effectiveness of the implementation of accounting information systems plus the implementation of good internal control, it will increase the prevention of accounting fraud